PROBLEMATIKA MENTAL ANAK PADA MASA PERTUMBUHAN DAN PERKEMBANGANNYA - Sitti Trinurmi (240-540X)
There are several factors that cause the emergence of mental disorders of children during their growth and development, among others; lack of nutrition, parental behavior, poor hygiene, an environment that is not conducive, the result can cause several kinds of disorders, both physical and psychological, including; impaired motor development. language development disorders, mental reterdation, celebral palsy, sindrown down and autism disorders. To help overcome the mental problems of children in their growth and development, there are several services that must be provided, namely student understanding services (data collection), information provision services, advisory services, placement services, problem solving and habituation services. This service is tailored to the approach of the crisis approach, remedial approach, prefentive approach, and development approach. Also instructional and interactive education approaches, systems support approaches and personal development approaches